Histopathological and Molecular study of effects of potassium dichromate on kidney of the male mice - Nuha Shaker Ali (International Journal of Medical Toxicology and Legal Medicine, 2024)
Potassium Dichromate is inorganic reagent, work as an oxidizing agent in several industrial and laboratory applications. Potassium Dichromate is harmful to health at the acute and chronic status in animals and human. Potassium Dichromate is red-orange color, very bright, and crystalline ionic solid. Aim of the current study is determine the histological changes in the kidney and determine the gene expression molecular changes for some genes in mice which administrated potassium dichromate. Twenty male mice, divided into two groups, each group consist of ten mice. The first group administrated potassium dichromate (67) Mg/kg/BW, for 21 day orally, while the second group (control group was administrated distal water. The results showed that the histopathological changes of the first group (treated by potassium dichromate) are included atrophy of glomeruli of the kidney, vascular dilatation, and necrosis, while the second group (control group) showed that normal glomeruli of the kidney, normal proximal, distal and convoluted tubules. The gene expression of NR3C1 gene are decrease in the first group (treated by potassium dichromate) than in the healthy group. In addition to that, the first group (treated by potassium dichromate) showed that increase TP53 gene expression than in the healthy group. Finally, the potassium dichromate causes pathological changes in the renal tissues in the male mice with changes in gene expression of NR3C1 gene, and TP53 gene by decrease the first gene and increase the second gene.